Evaluasi Usability Website Dinas Perpustakaan dan Kearsipan Provinsi Jawa Timur menggunakan Metode Usabiltity Testing - Yoelius Ramadhan Pamungkas; Buce Trias Hanggara; Bondan Sapta Prakoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The website of the Department of Library and Archives of East Java Province was developed to be used as a medium for the public to dig up information related to this library. However, it turns out that the website is still not perfect because there are still things that are not going well. This is known when researchers make observations on the website and conduct interviews with the bibliography, that the website is not yet perfect. Usability evaluation needs to be done to find solutions to the problems found. Usability testing is the right method for conducting this evaluation because it involves direct users and takes advantage of the use of the SUS questionnaire (system usability scale). There are five aspects of usability used in this study, namely efficiency, effectiveness, learnability, memorability, and satisfaction. Usability testing will be conducted on five respondents. In addition to testing, the five respondents will also be interviewed in order to explore usability problems that cannot be found if only based on testing. The results of the test found 23 problems. This problem will be analyzed in depth, which aims to determine the usability value on this website. The results of the data analysis also show that the aspects of efficiency, effectiveness, and satisfaction get a value that is below the standard, while on the aspects of learnability and satisfaction are good. Then from the results of the analysis, recommendations for improvement are made which are also based on the usability guidelines compiled by the U.S dept of health and human services in 2006 so that this website becomes easier and more convenient for users to use.